Where to turn?: A case study of Czech student and local advisor experiences of writing personal statements for undergraduate Anglophone admissions - Tavakoli, M (2018)
At the intersection of language learning and international student mobility, the personal statement (PS) in United States and United Kingdom university undergraduate admissions is often an English as a foreign language (EFL) learner’s first exposure to the use of English for academic purposes. This case study was inspired by an EFL secondary school student’s emotional experience confronting this challenge in the semi-peripheral context of the Czech Republic and designed around the hypotheses that this problem occurred because of a lack of familiarity with the PS genre in Czech- and EFL-writing instruction, a lack of PS information and resources, and unstructured PS feedback. In adopting a pragmatist stance, the study design aggregated practitioner voices to interrogate these hypotheses, as sources of the PS genre as a problem, and uncover solutions through research questions that probed (1) the student’s and three local Czech advisors’ experiences; (2) the input and feedback available from these local advisors and two Anglophone university gatekeepers; and (3) existing best practices. Semi-structured interviews, informed by narrative inquiry, served to elevate the six participants’ voices and incorporate contextual factors based on sociocultural theory and academic literacies. This study uniquely contributes to PS genre research in its juxtaposition of student, advisor, and gatekeeper voices, selected theoretical lenses, and attention to the Czech educational context and undergraduate admissions level. The narrative analysis findings confirm that the PS was problematic because of conflicts between aspects of the student’s Czech background and six identified features of the PS genre. The construction of knowledge networks and comparison of feedback provision demonstrate that input and feedback informed by genre expertise are not equally available in the Czech EFL context to address these conflicts and mediate emotional consequences. Given the pragmatist urgency to find solutions, participants’ pedagogical recommendations span PS input and feedback, and EFL teacher training.